Analysis of Students' Errors in Solving Algebraic Story Problems Based on Newman's Procedure: A Case Study in Junior High School - Saputra, Sandy; Anggraini, Anggraini; Sugita, Gandung; Idris, Mustamin (Jurnal Pendidikan MIPA, 2025)
This study aims to obtain a description of student errors in solving algebraic form story problems based on Newman's procedure in junior high school. This type of research is descriptive using a qualitative approach. This research uses Newman's error analysis. The subjects of this study were three students, each of whom had high mathematical ability (ST), medium mathematical ability (SS), and low mathematical ability (SR) selected from class VIII W.R Supratman based on the report card value of mathematics class VII odd semester 2023/2024. The results of this study are as follows: Students with high mathematical ability (ST) tend to make mistakes at the reading stage by not reading the problem completely, especially the symbol "Rupiah," and at the writing/notation (encoding) stage by not writing the conclusion and the symbol "Rupiah". Students with moderate mathematics ability (SS) made mistakes at the comprehension stage by not writing and mentioning the question information completely, the transformation stage by making an incorrect mathematical model, and the writing/notation (encoding) stage by not writing the "Rupiah" symbol. Students with low mathematics ability (SR) made mistakes at almost all stages: reading by not mentioning the Rupiah symbol and not reading the complete problem, comprehension by not writing and mentioning the problem information completely, transformation by making an incorrect mathematical model, process skills with calculation errors, and writing/notation (encoding) by not writing the Rupiah symbol and the correct conclusion. This research shows the importance of understanding the problem thoroughly, making the right mathematical model, and writing complete notations and conclusions in solving mathematical problems, the results of this study are expected to contribute to the improvement of the mathematics learning process, both from the teacher and student side, so as to improve students' mathematical problem solving skills, especially in the material of algebraic form story problems.       Keywords: problem solving errors, math skills, algebraic story problems, newman procedure.